ART Initiation for Infants Diagnosed With HIV Through Point of Care and Conventional Polymerase Chain Reaction Testing in Kenya: A Case Series - Wexler, Catherine (Pediatr Infect Dis J, 2021)
We sought to understand the sequence of testing and treatment among nine infants offered both conventional and point-of-care testing and diagnosed as HIV-positive by 6 months of age in Kenya. One infant received per protocol testing and treatment. Patient-level (late presentation, disengagement), provider-level (reluctance, error/oversight), and system-level (stock-outs, errors) challenges delayed diagnosis and treatment. Early point-of-care testing can streamline testing; however, challenges mitigate benefits.